1997
DOI: 10.1002/eji.1830270516
|View full text |Cite
|
Sign up to set email alerts
|

Signals through CD8 or CD4 can induce commitment to the CD4 lineage in the thymus

Abstract: Differentiation of thymocytes into mature single-positive T cells is an ordered process involving sequential interactions between T cell receptor (TCR), co-receptors (CD4 or CD8) and their appropriate major histocompatibility complex-encoded ligands. Precisely how these receptor/co-receptor engagements determine lineage commitment is still controversial, but recently it has been suggested that quantitative differences in the signal transmitted by co-ligation of CD4 versus CD8 with TCR might provide the discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 57 publications
4
34
0
Order By: Relevance
“…The data described in this report would support and extend this model in that the degree of ERK activation through the TCR sets thresholds for positive and negative selection. This would be in accordance with our previous finding that engagement of the TCR together with CD4 in very high concentrations did not lead to enhanced CD4 maturation but rather caused apoptosis of some DP thymocytes (41). The amount of lck activation and ERK signaling needed at a given time point to surpass the thresholds for positive or negative selection would depend on the integration of signals from other pathways such as the JNK or p38 signaling cascades.…”
Section: Discussionsupporting
confidence: 92%
“…The data described in this report would support and extend this model in that the degree of ERK activation through the TCR sets thresholds for positive and negative selection. This would be in accordance with our previous finding that engagement of the TCR together with CD4 in very high concentrations did not lead to enhanced CD4 maturation but rather caused apoptosis of some DP thymocytes (41). The amount of lck activation and ERK signaling needed at a given time point to surpass the thresholds for positive or negative selection would depend on the integration of signals from other pathways such as the JNK or p38 signaling cascades.…”
Section: Discussionsupporting
confidence: 92%
“…According to the current models of selection, strength and duration of TCR-mediated signaling determine lineage commitment or efficiency of selection of CD4 ϩ or CD8 ϩ T cells (47,54), whereby strong or long-lasting signals favor CD4 and weaker or short signals CD8 maturation. In particular, experiments using thymic organ culture (55,56) and Lck transgenic mice (57,58) have demonstrated that relatively small alterations in intrathymic Lck activity can significantly affect the CD4/CD8 lineage decision. Likewise, several studies using genetically modified mice and in vitro differentiation systems have shown that the strength/duration of Raf-Mek-Erk signaling regulates positive selection, lineage commitment, and negative selection (47).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have also reported that anti-TCR Ab restores the generation of CD4 ϩ CD8 Ϫ thymocytes in class II MHC-deficient FTOC (15,16). However, the in vitro culture system of FTOC did not allow us to examine whether the newly generated CD4 ϩ CD8 Ϫ thymocytes could emigrate the thymus to supply CD4 T cells in the periphery.…”
Section: Ifferentiation Of Immature Cd4mentioning
confidence: 97%